The effects of wood particle size and different process variables on the performance of steam‐oxygen blown circulating fluidized‐bed gasifier. Issue 3 (11th June 2014) - Kurkela, Esa; Kurkela, Minna; Hiltunen, Ilkka
<x xml:space="preserve">Abstract</x> Pressurized circulating fluidized‐bed gasification by steam‐oxygen has been developed at VTT for syngas applications. In this process, wood feedstocks are first converted into raw gasification gas, which is then filtered at about 600°C before catalytic reforming of tars and hydrocarbon gases. This article presents results of the gasification and gas filtration tests carried out with wood pellets, crushed pellets, bark, and crushed forest residues. The effects of operating pressure, bed material used, and other main operating variables were examined. Dolomite, magnesium oxide, and sand were used as bed materials. Gasification pressure was in the range 0.25–0.6 MPa and operating temperature 860–930°C. In best operating conditions, over 98% carbon conversion was achieved with very smooth long‐term operation. The feedstock particle size, operation pressure, and the presence of calcium‐based bed material had strong effects on tar formation and filter operability. © 2014 American Institute of Chemical Engineers Environ Prog, 33: 681–687, 2014